What determines state heterogeneity in response to US tariff changes? - Ana Maria Santacreu; Michael Sposi; Jing Zhang (Federal Reserve Bank of Chicago, 2023)
We develop a structural framework to identify the sources of cross-state heterogeneity in response to US tariff changes. We quantify the effects of unilaterally increasing US tariffs by 25 percentage points across sectors. Welfare changes range from −0.8 percent in Oregon to 2.1 percent in Montana. States gain more when their sectoral comparative advantage covaries negatively with that of the aggregate US. Consequently, "preferred" changes in tariffs vary systematically across states, indicating the importance of transfers in aligning state preferences over trade policy. Foreign retaliation substantially reduces the gains across states while perpetuating the cross-state variation.
Keywords: F11; F62; 330; Interstate trade; Gains from trade; Customs union